Characterization of betalains extracted from Bougainvillea (Bougainvillea spectabilis) as natural colorant for red calamansi juice. - Miramon, Janreich F.
The trend in the use of natural food colorants rose due to the harmful side effects in using artificial food colorants. The study aimed to extract a natural red colorant from Bougainvillea as a potential alternative for artificial colorants. The study aimed to extract a natural red colorant from Bougainvillea as a potential alternative for artificial colorants. Bougainvillea flower bracts were collected, steam blanched, extracted with water through homogenization, filtered and the liquid BRC was obtained. The stability of the BRC in chilled and ambient conditions was characterized in terms of betalain content, %TA and pH for 15 days. BRC was then utilized as a colorant for red calamansi juice. Fresh BRC contained 94.6±0.2 mg/100 of betalains, pH of 5.65±0.03 and %TA of 1.0%±0.00. The betalain content and pH of the samples stored at ambient conditions significantly decreased to 24.24±0.008 mg/100 g and 3.73±0.01, respectively, at Day 15 than the chilled samples. %TA of the samples stored at ambient conditions significantly increased to 12.68±0.2 mg/100g at Day 15. BRC was used as a colorant for red calamansi juice where the most preferred formulation was 2% (v/v) of the BRC. The juice was characterized to have French pink to Sasquatch socks color, imperceptible herbal odor and bitter taste of the BRC and a general acceptability rating of ?like very much?. Therefore, a red colorant can be extracted from Bougainvillea which can be applied to color calamansi juice and is generally stable at chilled conditions for 15 days. Further treatments, such as spray drying and addition of stabilizing agents is recommended for the BRC to further increase its stability.